Transition to adulthood: experiences of parents of young adults with developmental disabilities - Tobin, Rosemary C., author; Lehmann, Jean P., advisor; Spencer, Karen, committee member; Foster, Ann, committee member; Davies, Timothy Gray, committee member (Colorado State University. Libraries, 2003)
This study used a phenomenological approach to understanding the process of transition from the perspective of families of young adults with developmental disabilities. Some of the primary sources of the tension during transition appeared to be located in the family striving for a vision of quality life for the young adult and garnering the resources to achieve the vision. The main themes which emerged from the in depth interviews with nine families whose sons and daughters had developmental disabilities, included both internal themes, those which involved the family directly and external themes, those which had an impact on transition but were generated outside of the family system. The internal themes provided detail about the intensity and long-term nature of parent involvement during transition, the need to develop and maintain relationships, which support the young adult and the need to develop a vision of the future. The external themes were reflected in tension resulting from negotiating for services from educational systems and adult service agencies. Families in this study were going beyond filling in the gaps in the school and adult service systems. The experiences illustrate that families were the "net" under school transition services and adult living supports. They went beyond advocating and created their own options to fulfill their visions for a quality life in the community. For families in this study who had a member with a disability, the issue of quality of life is infused into the operation of the family system. Quality of life is a subtle yet powerful force influencing decisions. Quality of life theory can assist in understanding the motivations of families during the transition process as they strive to achieve a quality life for their sons and daughters. In contrast to the efforts of families focused on an individual, the systems families encounter are establishing programs for groups of people. Quality of life perspectives can provide a framework for the development of strategies and programs that are aligned with family values and designed to meet the needs of young adults with developmental disabilities.
Keywords: families and family life; personal relationships; sociology; continuing education; individual and family studies